2008
DOI: 10.22621/cfn.v122i3.608
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons and Trends in White-tailed Deer, <em>Odocoileus virginianus</em>, Body Fat in Northeastern Minnesota, 1974-1990

Abstract: The relationships among locations of body fats have not been thoroughly examined in White-tailed Deer (Odocoileus virginianus). We measured bone marrow fat (n = 2995), back fat (n = 1018), kidney fat (n = 2076), and xiphoid fat (n = 1246) levels of White-tailed Deer kills from Cook and Lake counties in northeastern Minnesota during [1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990]. For each dead deer we determined age, sex, date, and causes of mortality. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Hence, the nutritional status of individuals may have the potential to affect prey selection. In seasonally variable regions predator selection of prey may also be affected by weather-induced effects on prey vulnerability which may change as winter proceeds [12, 28, 29, 30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Hence, the nutritional status of individuals may have the potential to affect prey selection. In seasonally variable regions predator selection of prey may also be affected by weather-induced effects on prey vulnerability which may change as winter proceeds [12, 28, 29, 30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that wolf‐killed moose were not malnourished (Ballard et al , Hayes et al ) and no evidence of wolves selecting for individuals in poorer body condition compared to harvested individuals (moose; Sand et al ) or those hit by cars (mule deer and white‐tailed deer [ Odocoileus virginianus ], O’Gara and Harris ; roe deer [ Capreolus capreolus ], Gazzola et al ). On the contrary, Nicholson et al () reported white‐tailed deer killed by predators had lower bone marrow fat compared to those hit by cars. Body condition, and thus prey vulnerability, can also be affected by obvious factors such as injuries and arthritis (Peterson ) and by less obvious conditions such as malnutrition of parents or even grandparents (Mech et al , Côté and Festa‐Bianchet , Parker et al , Shallow et al ).…”
Section: Discussionmentioning
confidence: 95%
“…We note a few considerations and limitations of the visual index of nutritional condition. Deposition and mobilization of fat in the major reserves occurs simultaneously to some degree, but in general increments with disappearance of subcutaneous reserves occurring first (Kistner et al 1980, Nicholson et al 2008). Based on the general order of deposition and mobilization, an index of nutritional condition based on coverage of subcutaneous fat alone may not be indicative of extremely low or high nutritional condition (Cook et al 2007).…”
Section: Discussionmentioning
confidence: 99%